The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/ajh.24044
|View full text |Cite|
|
Sign up to set email alerts
|

The role of bone marrow biopsy and FDG‐PET/CT in identifying bone marrow infiltration in the initial diagnosis of high grade non‐Hodgkin B‐cell lymphoma and Hodgkin lymphoma. accuracy in a multicenter series of 372 patients

Abstract: Bone marrow infiltration (BMI), categorized as an extra-nodal site, affects stage and is associated with poor prognosis in newly diagnosed lymphoma patients. We have evaluated the accuracy of PET/CT and bone marrow biopsy (BMB) to assess BMI in 372 lymphoma patients [140 Hodgkin Lymphoma (HL) and 232 High Grade B-cell non-Hodgkin Lymphoma (HG B-NHL), among them 155 Diffuse Large B-Cell Lymphoma (DLCL)]. For HL cases, and taking into account PET/CT, sensitivity, negative predictive value (NPV) and accuracy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
31
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
9
31
2
1
Order By: Relevance
“…Diagnostic performance has been considered an argument to abrogate the routine use of BMB in this setting due to a claimed superiority of PET/CT. However, we and others have shown before that the performance of PET/CT in terms of sensitivity and accuracy was not as high as stated in other series [10,12,13]. To this regard, it has been proposed that this could rely in histologically unproven cases that could have been inappropriately considered true positives [12,19,21].…”
Section: Discussionmentioning
confidence: 77%
“…Diagnostic performance has been considered an argument to abrogate the routine use of BMB in this setting due to a claimed superiority of PET/CT. However, we and others have shown before that the performance of PET/CT in terms of sensitivity and accuracy was not as high as stated in other series [10,12,13]. To this regard, it has been proposed that this could rely in histologically unproven cases that could have been inappropriately considered true positives [12,19,21].…”
Section: Discussionmentioning
confidence: 77%
“…In a retrospective cohort study by Adams' own group, focally increased FDG uptake in the bone marrow was not prognostic for PFS or OS. However, because of the small number of patients the analysis is likely underpowered and 34/78(44%) of patients had PET/CT-detected bone marrow involvement, which is higher than usually reported [1,10,[13][14][15][16]. Our study supports an independent prognostic value of PET/CT-ascertained bone marrow involvement, but we do not "claim" prognostic irrelevance of BMB, as accused by Adams et al The fact that positive BMB was only prognostic in univariate analysis rather reflects the interplay with other important prognostic factors.…”
mentioning
confidence: 52%
“…This evokes the third objection by Adams et al We are aware that some previous studies, including large series and our own data, have shown suboptimal sensitivities of PET/CT to detect bone marrow involvement by BMB [13,16,18]. The Lugano classification recommends BMB in patients without evidence of bone marrow involvement by PET/CT and only if finding of a discordant histology is relevant for patient management [19].…”
mentioning
confidence: 89%
“…Marrow involvement in the advanced‐stage disease like DLBCL is usually sufficiently depicted by PET‐CT, and BM biopsy provides little additional staging information. However, BM biopsy is indicated when a PET/CT scan is negative . In another study, it was suggested BM biopsy could provide information in addition to BM involvement, such as information on the hematologic status of patients .…”
Section: Discussionmentioning
confidence: 99%